A study on prevalence and risk factors of depression among adolescent girls studying in government and private schools—A comparative study - Preethi Alex; D Sharon Cynthia; V Kanagalakshmi (Journal of Family Medicine and Primary Care, 2023)
Background: The prevalence of depression among school-going adolescent girls in India is about 40%. Adolescent girls attending private and government-run schools in South India have vastly different sociodemographic backgrounds and school environments. Assessing the associated risk factors for depression will help in designing appropriate preventive strategies. Objective: To evaluate the prevalence of depression among school-going adolescent girls and the associated risk factors among government and private school students. Methods: The cross-sectional comparative study was conducted in two private and two government-run schools in Tamil Nadu. A semi-structured questionnaire and 11-item Kutcher Adolescent Depression Scale were administered to female students belonging to grades eight, nine, and ten. Differences in the prevalence of depression and the familial, social, and behavioral risk factors between private and government school students were measured and analyzed. Results: The prevalence of depression among our study population is 23.8%. An adolescent girl studying in a private school has a 4.67 times higher chance of being depressed as compared to her counterpart in a government school. Stress due to higher academic expectations, peer pressure, disagreement with friends, excess smartphone usage, and family discord are associated factors in private school students, and family discord and chronic illness among family members were associated risk factors for depression in government school students. Conclusion: There is a wide disparity in the prevalence of depression and associated factors among private and government school-going adolescent girls. The intervention program for depression has to be addressed differently according to the type of school.